PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BEI - Siti Muntahanah; Heru Cahyo (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to examine the effect of Good Corporate Governance on firm value. The research method used in this research is quantitative research with sampling using purposive sampling technique. Based on the predetermined characteristics, a sample of 13 health sector companies listed on the Indonesia Stock Exchange with a research period of 2017-2021 was obtained. The type of data used is secondary data and the analysis method used is panel data regression, using Eviews. The results of this study indicate that the variables of Institutional Ownership and Public Ownership have a positive and significant effect on firm value, while the variables of the Board of Independent Commissioners and the Audit Committee have a negative and insignificant effect on firm value. Advice for investors, investors should pay attention to the performance of a company before investing by looking at its governance. For the company, it is hoped that the management will be able to carry out their duties and roles optimally in order to create good management quality in order to obtain a good assessment from investors.